Underestimation of mitochondrial respiratory capacity in gray matter voxels of the human brain map due to limited OXPHOS and TCA cycle in astrocytes - Chinopoulos, Christos (Frontiers in Cellular Neuroscience, 2025)
Considering that the aerobic energetic landscape of the brain is shaped by its mitochondria, Mosharov et al. generated an atlas of mitochondrial content and enzymatic OXPHOS activities at a resolution comparable to MRI by physically voxelizing frozen human brain tissue. However, astrocytes in the adult human brain lack expression of several TCA cycle and OXPHOS enzymes. Therefore, their formula expressing mitochondrial respiratory capacity (MRC) -defined as tissue respiratory capacity normalized to mitochondrial density- underestimates actual values by a factor proportional to the square root of the fraction of respiration-capable cells (primarily neurons) in gray matter voxels.